(untitled) (Al-Qamar, 2019)
Islam gives us the concept of humility in the face of pride and arrogance and self-respect in the face of inferiority complex. Humility does not mean feeling inferior, but acknowledging one’s inferiority to God Almighty. A humble person considers his every success not the result of his abilities but the grace of his Lord and prostrates before him. He gives others the status they deserve. Islam commands us to respect one another. The Prophet (peace and blessings of Allah be upon him) in his Farewell Sermon described the honor of a human being as honorable as Ka’bah. A person suffering from inferiority complex should think that even if he has faced failure once but he has also achieved success many times in his life. This is the world in which he is walking, this is the grace of Allah Almighty upon him. He who does not have shoes should not look at those who wear shoes, but look at him who has no feet.